Magneto-nanosensor platform for probing low-affinity protein–protein interactions and identification of a low-affinity PD-L1/PD-L2 interaction - Jung-Rok Lee (Nature Portfolio, 2016)
Measurement of low-affinity protein–protein interactions is challenging; surface plasmon resonance requires high concentrations of reagents. Here the authors combine magneto-nanosensors with microfluidic chips and protein-conjugated magnetic nanoparticles to discover a low-affinity interaction between T-cell inhibitory receptors PD-L1 and PD-L2.